Stability of Single-Parent Gene Expression Complementation in Maize Hybrids upon Water Deficit Stress. Issue 2 (20th December 2016) - Marcon, Caroline; Paschold, Anja; Malik, Waqas Ahmed; Lithio, Andrew; Baldauf, Jutta A.; Altrogge, Lena; Opitz, Nina; Lanz, Christa; Schoof, Heiko; Nettleton, Dan; Piepho, Hans-Peter; Hochholdinger, Frank
Abstract : Single-parent expression genes are nonsyntenic and stable throughout fluctuating water availability, underscoring their role in the early developmental manifestation of heterosis in maize. Abstract: Heterosis is the superior performance of F1 hybrids compared with their homozygous, genetically distinct parents. In this study, we monitored the transcriptomic divergence of the maize ( Zea mays ) inbred lines B73 and Mo17 and their reciprocal F1 hybrid progeny in primary roots under control and water deficit conditions simulated by polyethylene glycol treatment. Single-parent expression (SPE ) of genes is an extreme instance of gene expression complementation, in which genes are active in only one of two parents but are expressed in both reciprocal hybrids. In this study, 1, 997 genes only expressed in B73 and 2, 024 genes only expressed in Mo17 displayed SPE complementation under control and water deficit conditions. As a consequence, the number of active genes in hybrids exceeded the number of active genes in the parental inbred lines significantly independent of treatment. SPE patterns were substantially more stable to expression changes by water deficit treatment than other genotype-specific expression profiles. While, on average, 75% of all SPE patterns were not altered in response to polyethylene glycol treatment, only 17% of the remaining genotype-specific expression patterns were not changed by water deficit. Nonsyntenic genes that lack syntenic orthologs in other grass species, and thus evolved late in the grass lineage, were significantly overrepresented among SPE genes. Hence, the significant overrepresentation of nonsyntenic genes among SPE patterns and their stability under water limitation might suggest a function of these genes during the early developmental manifestation of heterosis under fluctuating environmental conditions in hybrid progeny of the inbred lines B73 and Mo17.